Separation of Zr from Hf in acidic chloride solutions by using TOPO and its mixture with other extractants - Banda, Raju; Lee, Hwa Young; Lee, Man Seung (SPRINGER, 2013)
Liquid-liquid extraction of Zr and Hf from chloride solutions was performed by using TOPO extractant in kerosene. An effective extraction of Zr from Hf was achieved selectively at 2.5-3 M HCl condition. Moreover, a mixture of TOPO with DOS, D2EHPA, Aliquat 336, Alamine 336 and Alamine 308 were tested in order to investigate the extraction behavior of Zr and Hf. The mixture of TOPO and D2EHPA was found to increase the extraction of Zr and Hf. In the extraction by the mixture of TOPO and amine, the extraction percentage of Zr and Hf was decreased with the increase of amine concentration due to the preferential extraction of HCl. Finally, among the mixtures of TOPO and other extractants tested in this study, the TOPO alone system was found to be better for the mutual separation of Zr and Hf in hydrochloric acid media.
Keywords: SOLVENT-EXTRACTION; HAFNIUM SEPARATION; ZIRCONIUM; MEDIA